KUALITAS AUDIT DAN AUDITOR SWITCHING TERHADAP MANAJEMEN LABA - Muchran, Muchriana; Wardani, Ayu Eka; Alayda, Fifi Citra; Pratiwi, Fadhila Reskyta (IJMA (Indonesian Journal of Management and Accounting), 2024)
This study aims to analyze how the effect of audit quality and auditor switching on earnings management, besides that researchers will also examine the factors of auditor switching. This research uses quantitative research with a descriptive approach. Quantitative research was chosen because it aims to test the research hypothesis that has been proposed. Descriptive approach is a method based on the philosophy of positivism, used to examine a particular population or sample. The object of research is property, real estate and construction companies listed on the Indonesia Stock Exchange in 2021 - 2023 The population used is real estate and property companies listed on the Indonesia Stock Exchange (IDX) The research period used is 2021 - 2023. From this population, a sample will be taken as the object of research. The results showed that audit quality has a significant effect on earnings management, auditor switching has no negative effect on earnings management, and audit quality and auditor switching simultaneously affect earnings management in manufacturing companies in the real estate and property sub-sectors listed on the IDX for the period 2021 - 2023. The magnitude of the influence of each independent variable on the dependent variable, namely audit quality and auditor switching on earnings management in Real Estate and Property Sub-Sector Manufacturing Companies.